INTRODUCTION OF INNOVATIVE TECHNOLOGIES MANAGEMENT - L. Karapetyan; I. Kogotkova (Вестник университета)
The article is devoted to technological innovation, the problems of their implementation at the sectoral level and the level of construction organizations, the analysis of technological innovation today, а comparison with foreign experience innovation.